2015
DOI: 10.1007/s10461-015-1255-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing and Cross Border Migrant Vulnerability: Social Integration and Legal/Economic Status Among Cross Border Migrant Workers in Thailand

Abstract: The objective of this paper was to identify factors related to the use of HIV testing among cross border migrants in Thailand. Two measures of vulnerability (social integration and legal/economic status) as well as HIV knowledge, risk behaviour, and demographic factors were tested for association with HIV testing. Data were drawn from a survey of 2600 sexually active migrants age 15-59 in multiple provinces of Thailand. The measures of social integration (AOR = 1.14(95 % CI 1.09, 1.20) female; AOR = 1.12 (95 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…These findings are similar to research in Thailand which found that male migrants who had sex with a non-regular sex partner were more likely to receive HIV testing (31). Though it is not possible from the data we gathered to tell with whom participants have been sexually active, because many of the migrants in this sample had spouses who did not come with them to Kazakhstan, it is quite possible that they may be having sex with extra-marital partners while working in Kazakhstan.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are similar to research in Thailand which found that male migrants who had sex with a non-regular sex partner were more likely to receive HIV testing (31). Though it is not possible from the data we gathered to tell with whom participants have been sexually active, because many of the migrants in this sample had spouses who did not come with them to Kazakhstan, it is quite possible that they may be having sex with extra-marital partners while working in Kazakhstan.…”
Section: Discussionsupporting
confidence: 87%
“…MWs without legal status may be reluctant to use available public health services due to fear of deportation. Similarly, income can be a barrier to accessing health services for MWs unaware of low or no cost health programs [ 7 , 8 ]. There are a number of other factors, such as poor educational level and limited Thai language ability, that interplay to shape the vulnerability of MWs [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individual child factors include sex, age, and health status (chronic disease/disability) [ 28 , 30 ]. For migration factors, pertaining to both the household factors and the child's characteristics, factors include immigrant or legal status and work permit statuses of migrant parents, length of stay in the destination country which is related to the level of social integration of the migrant household in the destination country, previous migration experiences or migration history, plans for the length of stay in the country of destination and return to the country of origin [ 4 , 25 , 31 34 ].…”
Section: Methodsmentioning
confidence: 99%